Katalog der mittelalterlichen Handschriften der Zentral- und Hochschulbibliothek Luzern - Kamber, Peter Heinrich; Mangold, Mikkel (2019)
This catalogue describes en detail content, material character, genesis, and history of 115 medieval manuscripts from the fields of theology, liturgy, canon law, church history, history, literature, rhetoric, medicine, and law